EIB Working Papers 2019/03 - Financing and obstacles for high growth enterprises The European case (Volume 2019/3) - Pal, Rozalia (2019)
Firms can be identified as high growth, stable or declining. This paper investigates the links between these different phases in the life of a firm, investment activity, financing needs and financing constraints. Using the representative EIBIS survey of EU companies, it finds that firms in a high growth phase are more likely to apply for equity financing and more likely to be financially constrained. Further, it identifies firms with a high growth potential. The most severe barriers for high-growth enterprises are the availability of skilled staff and business regulations, while potential high-growth enterprises are more constrained by uncertainty about the future.